Thinking in systems : a primer - Meadows, Donella H.; Wright, Diana, 1961- (White River Junction, Vt. : Chelsea Green Pub., 2008)
"Thinking in Systems is a concise and crucial book offering insight for problem solving on scales ranging from the personal to the global. Edited by the Sustainability Institute's Diana Wright, this primer brings systems thinking out of the realm of computers and equations and into the tangible world, showing readers how to develop the systems-thinking skills that thought leaders across the globe consider critical for 21st-century life."--Jacket
Introduction: The systems lens
Part I: System structure and behavior. The basics ; A brief visit to the systems zoo
Part II: Systems and us. Why systems work so well ; Why systems surprise us ; System traps, and opportunities
Part III: Creating change
in systems and in our philosophy. Leverage points: places to intervene in a system ; Living in a world of systems
Appendix: System definitions: a glossary ; Summary of system principles ; Springing the system traps ; Places to intervene in a system ; Guidelines for living in a world of systems ; Model equations.
Includes bibliographical references (p. [208]-210) and index.
ARC
Book finder
Keywords: System analysis -- Simulation methods; Decision making -- Simulation methods; Critical thinking -- Simulation methods; Sustainable development -- Simulation methods; Social sciences -- Simulation methods; Economic development -- Environmental aspects -- Simulation methods; Population -- Economic aspects -- Simulation methods; Pollution -- Economic aspects -- Simulation methods; Environmental education -- Simulation methods